(3OQQ GdYHjQ Yf ZQQ GdJaSjQs - (3eMeO Hf MfHds
(3ChdgG (B:s
(3GdMeO ddg QH GdYGdejf ShQI GdHbQI (B_ (3eOfjI (B" (3Cde (B" (3, GdCUM Cf gPg GdMQha GdebWYI eG ESJCKQ Gddg HYdeg , hbGd LeghQ GdYdeGA c jLhR Cf jJcde ajgG hYf Ydi CfgG gi GSe Gddg GdC(B'(3Xe (B" (3dGQjH ajg (B" (3, Ci dGTc ajg s
(3BNQgG (B:s
(3jfJgi gPG GdLRA ai CKfGA GdMOjK Ydi BjI Gdcga (B:" (3bd EfeG CfG HTQ eKdce jhMi Edi CfeG Edce Edg hGMO (B" (3hgj GdBjI GdCNjQI ai GdShQI s
(3GdfSNI HgG MhGTs
(3HgG fXGe GdJYbjHIs
(3YdjgG MhGTis
(3MhGa GdChQGb eJbUaI s
(3cJHJ HYV YHGQGJgG HGdMeQI s
(3dNU HgG eDdagG YOOkG ef GdJaGSjQ (B: (3GdLdGdjf hGdHjVGhi hGdKYGdHi hGdHZhi hZjQgG s
Keywords: (3GdJaSjQ hYdhe GdbQBfs